Ulug’murodov Umirbek - Roza Eshbaeva Rustam qizi; Khamitov Eldor Erkinovich (TADQIQOTLAR.UZ, 2024)
Abstract: Romeo and Juliet is a play by William Shakespeare, written around 1594–1996. The play has been shown in many ways, like in books, songs, dances, and plays. Romeo and Juliet are seen as the classic example of lovers facing tough fate. The play happens in Verona and tells the tale of a big fight between two families, the Montagues and the Capulets. This fight leads to sad endings for Romeo and Juliet, the main characters. The story shows how love and a hidden wedding stand against hate and payback. It makes Romeo and Juliet, who are deeply in love but are from rival families, become mature fast and sadly die feeling hopeless.